Peran Guru BK dalam Meningkatkan Kedisiplinan Peraturan Siswa di SMA Wahid Hasyim Model - Muhammad Syafiq Mubahrok; Muhammad Syahroni Ramadhan; Selvi Asmara Yeni (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2025)
This study aims to examine and describe the role of Guidance and Counseling teachers in enforcing school discipline in Wahid Hasyim Model High School. This research was conducted based on interviews with Guidance and Counseling teachers where there were several students who did not obey the rules at school, such as students who arrived late, their clothes were removed and dating in class. The purpose of this study is that the researcher wants to find out how the role of Guidance and Counseling teachers in enforcing student discipline. This research uses a qualitative approach, meaning that the research aims to understand case studies about what the research subjects experience, for example, behavior, perception, motivation and other actions. based on the results of interviews with Guidance and Counseling teachers, there were violations of school regulations, with the existence of the order team for violators of this regulation, there was a decrease. The data collection techniques used are interviews, observations and documentation. And for techniques in data analysis, namely by reducing data and conclusions and data collected in check to absanya by using source triagulation. The results of the study show that the discipline of students at Wahid Hasyim Model High School is still fairly undisciplined, as evidenced by the existence of students who still violate the rules. The role of Guidance and Counseling teachers in enforcing discipline is to provide reprimands and advice to students who violate school regulations then cooperate with the order team and other teachers, the order team that provides punishment to students who are late and if the student has been neglected often commits violations at school such as arriving late, the student will be called to the counseling guidance room to be asked for information or individual counseling and the Guidance and Counseling teacher will contact the family for information.